Retention of Pro-vitamin A Carotenoids in Ogi Powder as Affected by Packaging Materials and Storage Conditions - Awoyale, W.; Maziya-Dixon, B.B.; Menkir, A. (Science and Education Publishing Co., Ltd., 2016)
The effect of different packages and storage conditions on the retention of pro-vitamin A carotenoids (pVAC) in ogi powder produced from yellow-seeded maize was investigated to study its storage stability on micronutrient retention. The ogi powder produced was packaged in a high-density polyethylene bag (HDPE), a polypropylene woven sack (PP), and a polyvinyl chloride container (PVC), and stored in different conditions for 12 weeks with sampling done at three-week intervals for pVACanalysis. At the end of the storage period, ogi powder packaged in HDPE stored outside the storage box had the highest percentage retention (31.32%) of trans-β-carotene and that packaged in PVC container stored in the lighted compartment had the least (21.57%). Therefore, HDPE could be a good package for the retention of trans-β-carotene (which is the most bioactive) in ogi powder when stored at a temperature of 27°C and relative humidity of 73%.